PENGELOLAAN PEMBELAJARAN AKUNTANSI YANG KREATIF DI SMK SULTAN AGUNG TIRTOMOYO WONOGIRI - ARYATI, AFNI ZWESTINA (2011)
General purpose of this research is describing creative accounting learning management in SMK Sultan Agung Tirtomoyo Wonogiri. Specific purposes are: (1) describing creative accounting learning class layout characteristic in SMK Sultan Agung Tirtomoyo Wonogiri, (2) describing teacher activities character in creative accounting learning in SMK Sultan Agung Tirtomoyo Wonogiri (3) describing creative accounting learning interaction character in SMK Sultan Agung Tirtomoyo Wonogiri. This research is a qualitative research. Research has done in SMK Sultan Agung Tirtomoyo Wonogiri. Collecting data technique uses participated observation, interview, and documentation. Analysis in qualitative research includes three main components which are data reduction, data presentation, and decision making with the verification. Research results are (1) theory classroom layout uses to present accounting theories and other studies arranged in classical, while accounting vocational program functions as learning activity implementation place: documenting and accounting cycle manually and computerizationally. (2) teacher activities in accounting learning include learning planning, learning implementation, and learning evaluation. Learning evaluation is done in theory and practice. Assessment activity is done through academic level assessment and worksheet. (3) teacher manages interaction well, it is between teacher and students, and all students both in theory classroom or practice classroom.